2015
DOI: 10.1016/j.atherosclerosis.2015.04.294
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the presence of the “deleted” miR-122 gene in HepG2 cells

Abstract: Aim: MicroRNAs (miRs) are involved in regulation of gene expression and may play a role in development of hypertension.Methods: Three months old C57BL/6J mice were treated angiotensin II (AngII, 490ng/kg/min) or control buffer using miniosmotic pumps for 2 weeks. Isolated RNA from aorta and perivascular adipose tissue (PVAT) was reverse transcribed using Megaplex primer pools and profiled with TaqMAn Rodent microRNA Array. Statistical tests were performed on normalized CT values in R (HTqPCR package) or DataAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Like miR‐122, miR‐122* is decreased in hepatocellular carcinoma compared to nontumoral liver, suggesting that the inhibition of transcription very likely takes place at the primary miR level. Why this happens has not been investigated in this context yet, but the work of Hamad and colleagues suggests that epigenetic silencing (identified in HepG2 cells) could be a possible mechanism . In other cases, where the ratio between the two strands is changed, different mechanisms have been proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Like miR‐122, miR‐122* is decreased in hepatocellular carcinoma compared to nontumoral liver, suggesting that the inhibition of transcription very likely takes place at the primary miR level. Why this happens has not been investigated in this context yet, but the work of Hamad and colleagues suggests that epigenetic silencing (identified in HepG2 cells) could be a possible mechanism . In other cases, where the ratio between the two strands is changed, different mechanisms have been proposed.…”
mentioning
confidence: 99%
“…Why this happens has not been investigated in this context yet, but the work of Hamad and colleagues suggests that epigenetic silencing (identified in HepG2 cells) could be a possible mechanism. (5) In other cases, where the ratio between the two strands is changed, different mechanisms have been proposed. For example, Winter and Diederichs showed that in the case of Let-7a the guide-to-passenger strand ratio can be actively regulated by Human Argonaute 3, which specifically enhances the passenger strand expression.…”
mentioning
confidence: 99%